PENGARUH UMUR POHON INDUK, UMUR TUNAS DAN JENIS MEDIA TERHADAP PERTUMBUHAN STEK PUCUK SUKUN - Hamdan Adma Adinugraha (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2011)
The study was conducted to develop methods for planting stock production by shoot cuttings. The objectives of the study were to identify the effect of parent tree age, shoot age and rooting media on the growth of shoot cuttings. The study was conducted in 2 experimental steps. The first was to examine the effect of parent tree age and shoot age on the groeth of cutting: parent tree age class of 5 years (KU-1), 6-10 years (KU-2), 11-15 years (KU-3) and 16-20 years (KU-4), and shoot ages of 3 and 4 months. The second was to test 6 rooting media types (volcanic sands, soil, rice husk charcoal, coconut husk, sand + rice husk charcoal/4:1 and sand + coconut husk/4:1). The results showed that shoot cuttings from root cuttings grew successfully. It reached 90-100% of survival rate. Parent tree age and shoot age significantly influenced the number of roots with the highest root number was 5,42 from 4 months shoot taken from KU-4 root cuttings. Types of media significantly affected rooting rate with the best was 98% shown in sand + rice husk charcoal (4:1) media.